Republic of Mozambique : Fifth Review Under the Policy Support Instrument, First Review Under the Twelve-Month Arrangement Under the Exogenous Shocks Facility, and Request for Modification of Assessment/Performance Criteria-Staff Report and Press Release. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses key findings of the Fifth Review Under the Policy Support Instrument for Mozambique, and findings of the First Review Under the Exogenous Shocks Facility. The country's track record of prudent policies has provided ample space for easing macroeconomic policies in 2009. Revenues surpassed expectations in the first semester and the fiscal program was on track at end-September, although the government missed its end-June 2009 assessment/performance criterion on net domestic credit very marginally. The government has reiterated its commitment to its medium-term strategy of prudent macroeconomic policies.